Pricing and Publishing Models of Electronic Journals - Moghaddam, Golnessa Galyani (Journal of Information and Knowledge, 2014)
There has been a crisis in scholarly communication since the late 1980’s due to the spiraling costs of scientific journals. Libraries were the first to experience the effects of the breakdown as they struggled to keep up with the exploding volume and cost of journals in Science, Technology, and Medicine (STM). As the cost of serials in major libraries soared, libraries were forced to cancel millions of dollars worth of subscriptions. Most pricing and publishing models were created to offer a constructive response to this issue. The aim of these initiatives is to transform scientific journal publishing into a market-aware and fiscally responsible enterprise. There are many pricing and publishing models for electronic journals. This paper has explained the following models: TULIP, PEAK, SPARK, BioOne, HighWire Press, Project MUSE, JSTOR, PubMed, and EPIC.